A Straightforward Random Walk Model for Fast Push‐Pull Tracer Test Evaluation. Issue 1 (23rd June 2016) - Klotzsch, Stephan; Binder, Martin; Händel, Falk
Abstract: In this article, we present a straightforward random walk model for fast evaluation of push‐pull tracer tests. By developing an adaptive algorithm, we overcome the problem of manually defining how many particles have to be used to simulate the transport problem. Beside this, we validate the random walk model by evaluating a push‐pull tracer test with drift phase and confirm the results with MT3DMS. The random walk model took less than 1% of computational time of MT3DMS, thus allowing a remarkable faster evaluation of push‐pull tracer tests. Abstract : Article Impact Statement: Hundred and fifty times faster assessing push‐pull tests by using a specialized model for users with commercial and scientific background.